Brazilian minipig as a large-animal model for basic research and stem cell-based tissue engineering. Characterization and in vitro differentiation of bone marrow-derived mesenchymal stem cells (Journal of Applied Oral Science, 2014)
Stem cell-based regenerative medicine is one of the most intensively researched medical issues. Pre-clinical studies in a large-animal model, especially in swine or miniature pigs, are highly relevant to human applications. Mesenchymal stem cells (MSCs) have been isolated and expanded from different sources. Objective: This study aimed at isolating and characterizing, for the first time, bone marrow-derived MSCs (BM-MSCs) from a Brazilian minipig (BR1). Also, this aimed to validate a new large-animal model for stem cell-based tissue engineering. Material and Methods: Bone marrow (BM) was aspirated from the posterior iliac crest of twelve adult male BR1 under general anesthesia. MSCs were selected by plastic-adherence as originally described by Friedenstein. Cell morphology, surface marker expression, and cellular differentiation were examined. The immunophenotypic profile was determined by flow cytometry. The differentiation potential was assessed by cytological staining and by RT-PCR. Results: MSCs were present in all minipig BM samples. These cells showed fibroblastic morphology and were positive for the surface markers CD90 (88.6%), CD29 (89.8%), CD44 (86.9%) and negative for CD34 (1.61%), CD45 (1.83%), CD14 (1.77%) and MHC-II (2.69%). MSCs were differentiated into adipocytes, osteoblasts, and chondroblasts as demonstrated by the presence of lipidic-rich vacuoles, the mineralized extracellular matrix, and the great presence of glycosaminoglycans, respectively. The higher gene expression of adipocyte fatty-acid binding protein (AP2), alkaline phosphatase (ALP) and collagen type 2 (COLII) also confirmed the trilineage differentiation (p